Structure of Welded Joints Obtained by Contact Weld in Nanostructured Titanium - Klimenov V. A. Vasily Aleksandrovich; Klopotov A. A.; Gnyusov S. F. Sergey Fedorovich; Vlasov V. A.; Lychagin D. V.; Chumaevskii A. V. (2015, 2015)
Title screen